5.6-nm p(+)/n junction formation for sub-0.05-mu m PMOSFETs by using low-energy B10H14 ion implantation - Park, HS; Jeong, KH; Suh, HW; Jung, HJ; Choi, WK (KOREAN PHYSICAL SOC, 2004)
Decaborane (B10H14) cluster ions were implanted into n-Si(100) substrates to fabricate shallow p(+)/n junctions. Implant energies of 2 keV, 5 keV, and 20 keV, equivalent to implant energies of the monomer boron ion of 174 eV, 435 eV, and 1.74 keV, respectively, were used at dosages of 1 X 10(12)/cm(2) and I x 10(13)/cm(2). The implanted samples were then subjected to activation annealing at 800 degreesC, 900 degreesC, and 1000 degreesC for 10 s. By using secondary ion mass spectrometry (SIMS) depth profiles, we determined that the depth of the shallow junction (D-s) at a dosage of 1 X 10(13)/cm(2) was in the range 12 nm - 45 nm after annealing at 1000 degreesC. D-s and transient enhanced diffusion (TED) were greatly reduced at implant energies lower than 3 keV, but thermal diffusion (TD) smoothly decreased. In particular, TED was suppressed in the p(+)/n junction implanted at 2 keV and a dosage of 1 X 10(13)/cm(2), and the formation of only a 5.6-nm ultra-shallow junction was identified. This kind of extreme suppression of D-s is thought to result from the formation of well-localized damage with few interstitial defects, which act as a sinks, due to very low-energy cluster ion implantation near the surface region. The p(+)/n junction exhibited a leakage current density of 1.8 X 10(-12) A/mum(2) at -2 V.